Diagnosing Indonesia's Digital Connectivity Deficit: A Comparative Policy Analysis of the High-Cost and Low-Quality Paradox - Muhammad Rafii Naufal (Logistic and Operation Management Research (LOMR), 2026)
Indonesia stands at a critical interlude in its digital transformation. Despite achieving a high internet penetration rate of 79.5%, the nation exhibits a “quality paradox”: consumers pay more for slower, less reliable internet compared to their ASEAN peers. This study employs a qualitative comparative analysis of secondary data, applying a Comparative Market Analysis and a structured Peer-Aspiration Comparative Framework, to examine the structural factors associated with Indonesia’s telecommunications performance deficit. The findings suggest that the lag in internet quality is associated with three interrelated structural conditions: geographic deployment constraints, regulatory spectrum scarcity (particularly the 3.5 GHz band), and an oligopolistic market structure. By benchmarking Indonesia against Vietnam as a developmental peer and South Korea as an aspirational model, this study identifies policy and investment directions for improving Indonesia’s connectivity outcomes. It recommends that the government transition from an infrastructure builder to a market facilitator by reforming spectrum policies and enabling active infrastructure sharing, while telecommunication operators shift investments toward Quality of Experience (QoE). These directions aim to address the structural conditions underlying the digital participation ceiling and support Indonesia’s transition toward meaningful, high-quality connectivity.